Comparison of safety of loop ileostomy and loop transverse colostomy for low‐lying rectal cancer patients undergoing anterior resection: A retrospective, single institution, propensity score‐matched study. Issue 2 (21st March 2020) - Sun, Xiyu; Han, Huiqiao; Qiu, Huizhong; Wu, Bin; Lin, Guole; Niu, Beizhan; Zhou, Jiaolin; Lu, Junyang; Xu, Lai; Zhang, Guannan; Xiao, Yi
Abstract: Introduction: This study was to compare the prevalence of stoma‐related complications and stoma reversal perioperative complications of patients with low‐lying rectal cancer who received preventative loop ileostomy and those who underwent loop transverse colostomy. Methods: This retrospective single‐center study analyzed the clinicopathologic and surgical data of 288 patients with pathologically proven primary rectal cancer who underwent anterior resection with either preventative loop ileostomy ( n = 82) or loop transverse colostomy. To achieve comparability of a propensity score matching method was used to match patients from each group in a 1:2 ratio. Determinants of stoma‐related complications were analyzed by multivariate logistic regression analysis. Results: Forty‐nine (74.3%) patients in the loop ileostomy group experienced stoma‐related complications versus 48.7% in the loop transverse colostomy group ( P  < 0.01). Irritant dermatitis was the most frequent complication in both groups. The loop ileostomy group had a significantly higher rate (24.24%) of stoma reversal perioperative complications than the loop transverse colostomy group. Multivariate logistic regression analysis showed that ileostomy versus loop transverse colostomy was a significant independent risk for stoma‐related complications and stoma reversal perioperative complications. Furthermore, by Clavien–Dindo classification, patients receiving loop ileostomy had an overall higher rate of complications and stoma reversal perioperative complications versus those undergoing loop transverse colostomy ( P  < 0.01). The rate of grade II complications was significantly higher in the loop ileostomy group (43.9%) than that of loop transverse colostomy group (13.5%, P  < 0.01), whereas the rate of grade I, and grade IIIa and IIIb complications and stoma reversal perioperative complications was comparable between the two groups. Conclusion: The study has demonstrated that loop transverse colostomy is associated with significantly lower rates of stoma‐related complications and stoma reversal perioperative complications compared to loop transverse colostomy.